Structural influence line analysis program based on python - Amphon Jarasjarungkiat; Chaisiri Okoun; Praphaporn Silarach (AIP conference proceedings, 2021)
Analysis of influences line in structures that are complex or indeterminate will make the analysis difficult and time-consuming. Therefore, the researchers have developed an application to analyze beam structures in 2 dimensions that easy to use, convenient, and uncomplicated. In this research, the Double integration method and the Singularity function method are used to analyze the structure. Furthermore, Python is used to develop all of the instructions in Object-oriented programming (OOP) application development. The developed application is capable to analyze the influence lines of structures and display the results in form of animation to show load displacement and structural response. Moreover, it was incorporated with analysis to show basic structural diagrams such as bending, shear, and deflection diagrams. In the final word, this application will be a handy tool for better visualization and investigation behaviors of structures in actual design work.
Keywords: Advanced Sensor and Control Systems